2018
DOI: 10.1108/ijchm-06-2017-0333
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of hospitality CRM research

Abstract: Purpose This paper aims to comprehensively and systematically review the state of customer relationship management (CRM) research on hospitality and propose future research agenda. Design/methodology/approach All hospitality-related CRM articles since its introduction as a concept in 1988 were collected. The retrieved articles were then chronologically and thematically analyzed. Findings Hospitality CRM research has rapidly grown from the initial relationship marketing concept into social CRM. Five researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 91 publications
0
31
0
1
Order By: Relevance
“…It includes three publications: One review of the literature and two articles with a quantitative approach, all them with relationship about Customer Relation Management. Law et al (2018) realized a comprehensively and systematically review the state of customer relationship management (CRM) research on hospitality and propose a future research agenda. Law et al (2018) conclude in their review affirming than Hospitality CRM research has rapidly grown from the initial relationship marketing concept into social CRM and their identified five lines for future research: planning and implementation process, organizational support, technology and tools, customer perspectives and characteristics, and outcome and impact.…”
Section: Blue Cluster: Custom Relationship Management In the Hospitalmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes three publications: One review of the literature and two articles with a quantitative approach, all them with relationship about Customer Relation Management. Law et al (2018) realized a comprehensively and systematically review the state of customer relationship management (CRM) research on hospitality and propose a future research agenda. Law et al (2018) conclude in their review affirming than Hospitality CRM research has rapidly grown from the initial relationship marketing concept into social CRM and their identified five lines for future research: planning and implementation process, organizational support, technology and tools, customer perspectives and characteristics, and outcome and impact.…”
Section: Blue Cluster: Custom Relationship Management In the Hospitalmentioning
confidence: 99%
“…Law et al (2018) realized a comprehensively and systematically review the state of customer relationship management (CRM) research on hospitality and propose a future research agenda. Law et al (2018) conclude in their review affirming than Hospitality CRM research has rapidly grown from the initial relationship marketing concept into social CRM and their identified five lines for future research: planning and implementation process, organizational support, technology and tools, customer perspectives and characteristics, and outcome and impact. Rahimi and Gunlu (2016) researched chain hotel from the UK, where they applied a survey to managers to identified impacts of organizational cultures of consistency, adaptability, mission, and involvement on CRM implementation.…”
Section: Blue Cluster: Custom Relationship Management In the Hospitalmentioning
confidence: 99%
“…Padmavathy et al 2012describe CRM as a group of activities directed towards the customer and initiated at strategic level of the organization and based on technology aiming at improving interaction with customer to achieve customer loyalty and thus improving long term profits. According to Nyadzayo and Khajehzadeh (2016); Law, et al, (2018) CRM is based on creating and improving the relationship with customers in the most efficient way to keep them loyal and loyal customers are profitable. Sota, et al (2019) stated that due to the competitive business environment in the hotel industry nowadays, CRM has become a crucial tool that every hotel should use to survive in the market.…”
Section: Customer Relationship Management (Crm) and Loyaltymentioning
confidence: 99%
“…proposed. There have been limited applications of methodologies within CXM and it is suggested that more sophisticated and innovative methods should be adopted to improve research vigour (Boulding, Staelin, Ehret & Johnston, 2005;Law, Fong, Chan & Fong 2018).…”
Section: Future Research On the Extension Of Cxm To Cruise Passenger mentioning
confidence: 99%